Gambaran Keluhan Subjektif Pekerja Dan Tingkat Kebisingan Di Bengkel Bubut CV. X Surabaya - Rachmah Catur Agustin (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2021)
Background : The application of technology and the use of materials can lead to a potential hazard such as Occupational Diseases and work accidents that often appear in the workplace, namely noise. Purpose : To determine the noise level in the CV. X which can affect the complaints that affect the health of workers. Methods : The research was conducted by field observations and interviews with workers to obtain some primary data that support this research. Results: The results of the noise measurement still meet the Threshold Limit Value (TLV), but there is an influence in the form of complaints felt by workers such as dizziness, ringing in the ears, quick emotions or tired quickly, insomnia and nausea or vomiting. Conclusion : Noise level that meets the TLV physiologically does not interfere with the hearing canal, but can interfere with other health. Keywords : Noise, Complaints, Thershold Limit Value (TLV)